Cameron Kinchen: capstone - Kinchen, Cameron, artist (Colorado State University. Libraries, 2016)
The artist's statement: This is a collection of works from my capstone semesters here at Colorado State University. These works represent the knowledge I have gained during my classes within the Graphic Design field. Within my work I try to play with a wide variety of tools, techniques, and programs such as Adobe Illustrator, Photoshop, and After Effects. By doing so, I continuously evolve as an artist and stay up to day with today's design standards and trends. I also like to incorporate typography as much as possible within my pieces. As a designer I feel that it is important to understand and embrace typography within ones work and the world around us.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design